Safety, tolerability, pharmacokinetics, and pharmacodynamics of etrasimod in healthy Chinese adults: a randomized, double-blind, placebo-controlled dose-escalation phase 1 study - Wang, Fangfang; Niu, Xiaoye; Liu, Na; Zhu, Zhengying; Lin, Yun; Ying, Lisa; Li, Haiyan (Frontiers in Pharmacology, 2025)
ObjectivesEtrasimod is an investigational, oral, once-daily, selective S1P1,4,5 receptor modulator in development for the treatment of immune-mediated inflammatory diseases. We present safety, tolerability, pharmacokinetic, and pharmacodynamic results of etrasimod treatment in healthy Chinese adults.MethodsIn a Phase 1, randomized, double-blind, placebo-controlled, dose-escalation study, healthy Chinese adult subjects were randomly assigned to 3 cohorts. Cohorts 1 and 2 were given single-dose etrasimod, 1 mg or 2 mg, respectively, or placebo, followed by washout, then multiple-dose periods. Cohort 3 received multiple-dose etrasimod 2 mg or placebo, followed by titration to 3 mg or placebo. Cardiac monitoring included 24-h dynamic electrocardiogram, electrocardiogram monitoring, and 12-lead electrocardiogram. The primary endpoints were safety and tolerability, and secondary endpoints were pharmacokinetic and pharmacodynamic responses to etrasimod.ResultsAll treatment-emergent adverse events were Common Terminology Criteria for Adverse Events Grade 1 in severity, and all events were resolved without medical intervention. The most frequent event was sinus bradycardia (heart rate <50 bpm), and all these events were asymptomatic. No infections or infection-related events were reported. Pharmacokinetic and pharmacodynamic responses to etrasimod were consistent with previous studies in other populations. Etrasimod exposure increased at least dose proportionally for multiple doses and exhibited a half-life between 28.1 and 37.9 h. Etrasimod dose-dependently reduced lymphocyte counts, and these reductions were primarily seen in T naïve, T central memory, and T helper cells.ConclusionEtrasimod was safe and well-tolerated in healthy Chinese subjects up to 3 mg in single and multiple-dose periods.Clinical Trial Registrationhttp://www.chinadrugtrials.org.cn, identifier: CTR20190003.